Teori Kekuasaan Al-Mawardi: Analisis dan Implikasinya di Era Modern - Aisyah Syafitri Ilham; raehan firdaus; amanda zahra Nasution; adinda dara lubis; lantef widodo (Tabayyun : Journal Of Islamic Studies, 2025)
This article examines the classical Islamic political thought of Al-Mawardi, particularly his seminal work Al-Ahkam al-Sultaniyyah, which articulates a theory of power rooted in Islamic law and ethical governance. Al-Mawardi posits that leadership (imamah) is a divine trust aimed at preserving religion and regulating worldly affairs. His framework emphasizes justice, legitimacy, accountability, and the moral qualifications of rulers. Employing a qualitative approach through library research and content analysis, this study explores the relevance of Al-Mawardi's theory in the context of modern political systems, especially Indonesia's post-reform presidential democracy. The findings reveal that despite its theocratic origins, Al-Mawardi's principles can inform contemporary governance models when interpreted adaptively. This study contributes to the discourse on the intersection of Islamic governance and constitutional democracy, offering a contextual reading of classical Islamic norms in light of modern statehood. The article concludes that Al-Mawardi’s ideas remain significant in shaping political ethics in Muslim-majority societies, though practical implementation requires alignment with contemporary values such as human rights, pluralism, and citizen participation.